The case for a creator a journalist investigates scientific evidence that points toward God - Strobel, Lee, 1952-; Allen, Lad.; Allen, W. Peter; Kane, Tom.; Illustra Media (Firm); Carmel Entertainment Group, LLC. ([La Habra, CA] : Illustra Media, 2006)
Charts Lee Strobel's personal journey from spiritual skepticism to a profound faith in God.
DVD; widescreen (16:9); all regions; NTSC; stereo.
Narrated by Tom Kane.
Edited by Jerry Harned ; original photography, Jerry Harned ... [et al.] ; original music score by Mark Edward Lewis.
Based on the book The case for a creator / by Lee Strobel.
Special features: questions & answers; "How did life begin?"; "The machinery of life"; intelligent design resources; resources from Lee Strobel.
Keywords: Creationism; Religion and science; Bible and science; Evolution (Biology) -- Religious aspects -- Christianity; God -- Proof, Cosmological; Documentary videos; Religious videos